266 Are current guidelines for cervical sampling in hysterectomy specimens for endometrial cancer adequate?. (18th September 2019) - Nottley, S; Syed, S; Reed, N; Millan, D
Abstract : Objectives: To identify if sampling a single block from the centre of the cervix, including the anterior and posterior lips, is sufficient to detect cervical stromal invasion in hysterectomy specimens for endometrial cancers. We have expanded our study and have analysed according to grade and histological type. Methods: Our centre sequentially processes the entire endocervical canal in cases of endometrial cancer. We reviewed each block of cervical tissue in 79 cases in which there was known cervical stromal invasion; this was to ascertain if sampling only from the centre of the canal was adequate for detection. Results: Cervical stromal invasion is detected in only 73.5% (58/79) of cases when sampling only from the centre of the endocervical canal. Conclusions: Sampling only the centre of the endocervical canal fails to detect 26.5% of cases of cervical stromal invasion by endometrial cancer. We advise processing the entire endocervical canal to ensure correct staging.